Effect of thermomechanical processing defects on fatigue and fracture behaviour of forged magnesium - Andrew Gryguc; S.B. Behravesh; H. Jahed; M. Wells; B. Williams; R. Gruber; A. Duquett; T. Sparrow; M. Lambrou; X. Su (Fracture and Structural Integrity)
The microstructural origins of premature fatigue failures were investigated on a variety of forged components manufactured from AZ80 and ZK60 magnesium, both at the test specimen level and the full-scale component level. Both stress and strain-controlled approaches were used to characterize the macroscopically defect-free forged material behaviour as well as with varying levels of defect intensities. The effect of thermomechanical processing defects due to forging of a industrially relevant full-scale component were characterized and quantified using a variety of techniques. The fracture initiation and early crack growth behaviour was deterministically traced back to a combination of various effects having both geometric and microstructural origins, including poor fusion during forging, entrainment of contaminants sub-surface, as well as other inhomogeneities in the thermomechanical processing history.